A flowing conversation? Methodological issues in interviewing farmers about rivers and riparian environments. Issue 2 (2nd November 2018) - Thomas, Emma; Riley, Mark; Smith, Hugh
Abstract : Geographers are increasingly paying close attention to the importance of the place (and placing) of the research encounter. Research with farmers – who have been seen to hold very distinct people–place relations – is proving a particularly fruitful arena for developing these emplaced methodological discussions. To date, however, such emplaced methodological reflections with farmers have been largely terra‐centric, with relatively scant focus on rivers and riparian environments on farms. Within this paper we explore the methodological challenges of interviewing farmers about their lived experiences of, and perspectives on, rivers and riparian environments. We note how positionality is central to gaining access and suggest how performing the role of "geographical ignorance" can help simultaneously play the role of insider and outsider. We consider how engaging farmers in discussion about their riparian environments offers a different methodological challenge to engaging them in discussion of their land‐management practices as many struggle to articulate their knowledge of these environments and we reflect on how interview structure and being on and moving around the farm can act as a way of encouraging farmers' narratives of these spaces. Abstract : This paper explores the methodological issues and innovations in using interviews with farmers to examine rivers and riparian environments. The paper considers the importance of the emplacement of the interview approach.